Julie, or, The new Heloise : letters of two lovers who live in a small town at the foot of the Alps - Rousseau, Jean-Jacques, 1712-1778 (Rousseau, Jean-Jacques, 1712-1778. Works. 1990, 1997)
Rousseau's great epistolary novel, Julie, or the New Heloise, has been virtually unavailable in English since 1810. In it, Rousseau reconceptualized the relationship of the individual to the collective and articulated a new moral paradigm. The story follows the fates and smoldering passions of Julie d'Etange and St. Preux, a one-time lover who reenters Julie's life at the invitation of her unsuspecting husband, M. de Wolmar.